An Irrotational and Incompressible Flow Around a Body in Space (Journal of Partial Differential Equations, 1994)
We consider the problem of an irrotational and incompressible flow around a body in space. The basic existence is proved by formulating the problem into a variational problem. We also show that the solution is unique, and the maximum speed is attained on the body's boundary.